PENGARUH TATA KELOLA PERUSAHAAN TERHADAP PENGHINDARAN PAJAK - Puspita, Silvia Ratih; Harto, Puji (Diponegoro Journal of Accounting, 2014)
This paper examines the effect of corporate governance on tax avoidance. Corporate governance is proxied by the background of accounting or financial expertise of the audit committee, the proportion of independent directors, executive compensation, public ownership, and the largest shareholding. Tax avoidance is measured by performance-matched tax avoidance measure. By using purposive sampling in the observation period 2010-2012, obtained 399 observations from non-financial companies listed on the Indonesian Stock Exchange. Data were analyzed using ordinary least square regression model by incorporating the effect of year and industry sectors. Regression results show that public ownership and the largest shareholding have negative effect on tax avoidance. Company performance has positive effect on tax avoidance. Meanwhile, the background of accounting or financial expertise of audit committees, the proportion of independent directors, executive compensation, and company size do not have a significant effect on tax avoidance. The results of this paper indicate that some of the mechanisms of corporate governance in Indonesia are not effective according to their function for shareholders.